Opportunities and Problems Offered to Software Companies by the Pandemic Process - Acarer, Tayfun (ISRES Organizasyon Turizm Eğitim Danışmanlık Ltd. Şti., 2021)
The pandemic process is an event that we have never encountered in our lives, and it still continues as a reality that we do not know exactly when it will end. In fact, this problem experienced by individuals is also valid for all businesses. The pandemic continues to affect all sectors. Software is also one of the sectors affected by the pandemic. Although this influence has positive aspects, it also has serious negative aspects. Especially in this process, online working, information security, video conferencing systems, online education etc. While many new job opportunities have been provided for the software industry with many applications, a very significant need for experienced and qualified software developers has emerged. Especially the need for experienced software developers who can work independently and develop software has reached its peak in this process. These developments are seen in many countries in the world as well as in Turkey. Currently, the positive and negative effects of the pandemic on the software industry are felt much more aggressively in developed countries. As a result of this, there have been very serious transfers of experienced software developers to developed countries, especially in recent years.
Keywords: Pandemic; Software Companies; Software Engineers